Phospholipids and products of their hydrolysis as dietary preventive factors for civilization diseases - Karol Parchem (Postępy Higieny i Medycyny Doświadczalnej, 2016)
The results of numerous epidemiological studies indicate that phospholipids play an important role in the prevention of chronic diseases faced by contemporary society. Firstly, these compounds are responsible for the proper functioning of cell membranes, by ensuring liquidity and permeability, which is pivotal for normal activity of membrane proteins, including receptors. These mechanisms are at the core of prevention of cancer, autoimmune or neurological disorders. Secondly, structure and properties of phospholipids cause that they are highly available source of biologically active fatty acids. Thirdly, also products of endogenous hydrolysis of phospholipids exhibit biological activity. These include lysophospholipids formed as a result of disconnecting free fatty acid from glycerophospholipids in the reaction catalyzed by phospholipase A, phosphatidic acid and hydrophilic subunits released by the activity of phospholipase D. The bioactive products of hydrolysis also include ceramides liberated from phosphosphingolipids after removal of a hydrophilic unit catalyzed by sphingomyelinase. Phospholipids are supplied to the human body with food. A high content of phospholipids is characteristic for egg yolk, liver, pork and poultry, as well as some soy products. Particularly beneficial are phospholipids derived from seafood because they are a rich source of essential fatty acids of the n-3 family.